Clinical pharmacology of thyroid and antithyroid drugs - Stepanović-Petrović, Radica; Tomić, Maja (Archives of Pharmacy, 2022)
Autoimmune diseases accompanied by the development of hypothyroidism (Hashimoto’s thyroiditis) and hyperthyroidism (Graves’ disease) are one of the most common disorders of the thyroid gland. Hypothyroidism is a clinical syndrome that occurs as a result of thyroid hormone deficiency. Hyperthyroidism is excessive activity of the thyroid gland accompanied by hypersecretion of thyroid hormones. In simple terms, to achieve a euthyroid state in both clinical syndromes, two drugs are (most commonly) used - levothyroxine (hypothyroidism) and thioamide (hyperthyroidism). While it may seem simple, during the treatment, which is life-long in the case of hypothyroidism, patients should actually be carefully monitored, with the adjustment of the drug dose and the inclusion of other drugs for the treatment of comorbidities.